Peran Penyuluh Dan Strategi Pemasaran Dalam Meningkatkan Volume Penjualan Kelompok Nelayan Desa Madong Tanjungpinang - Lia Suprihartini; Roni Kurniawan (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2018)
This study discusses the role of extension agents and how marketing strategies are thought to affect the sales volume of the fishermen group in Tanjung Pinang village. In this study the role of instructor variables is seen from performance and competency indicators; marketing strategy seen from indicators of market segmentation, market positioning, market entry strategy, marketing mix; and sales volume of profit and sales indicators. This study uses the SPSS.V.24 program application, showing that partially the Sales Strategy has a positive and significant effect on Sales Volume and the Extension Role has a positive and significant effect on Sales Volume. Simultaneously the Extension Role and Sales Strategy have a positive and significant effect on Sales Volume